Carbon footprint information, prices, and restaurant wine choices by customers: A natural field experiment - Soregaroli, Claudio; Ricci, Elena Claire; Stranieri, Stefanella; Nayga, Rodolfo M.; Capri, Ettore; Castellari, Elena (Ecological economics, 2021)
Growing evidence suggests that consumers should be involved in the solutions to climate change. To test the responsiveness of wine consumers to carbon footprint stimuli we set a natural field experiment in a restaurant modifying the choice architecture of wine decisions. We modified wine cards to provide different information and price incentives to consumers to test the effects of two policy interventions for reducing CO2 emissions. Specifically, we test the provision of carbon footprint information and an additional price for carbon emissions. We randomly assigned subjects to four different wine cards. Results show that carbon footprint information alone is not enough to affect wine choices, but its effect becomes significant when combined with a price change. A card showing the carbon footprint of wine bottles and proportionally higher wine prices was associated with choices leading to lower carbon emissions. However, when information about the additional price to offset wine carbon emissions was made explicitly visible to consumers on another card, an opposite effect of an increase in the choice of wines with higher carbon-emitting production processes was observed. This finding indicates that how the price increase is presented can affect wine choices, highlighting the importance of careful information policy design.